Resources, Capabilities, Strategies and Competitive Advantage of Research University in Malaysia - Mohd Rosdi, Siti Asma’ (Management Research Journal, 2017)
This article identifies important elements acquired and bundled by Higher Education Institutions (HEIs) to attain competitive advantage. Competitive advantage is the crucial concept of sustainable development of Research University (RU). This article explores the competitive advantages of research university (RU) with a specific focus in the Malaysian context. The article guided by these questions - “What is competitive advantage?” and “What are competitive advantage elements for RU?” - in examining the resource, capability and strategy for RU. Using a qualitative method, interview was conducted. A qualitative thematic strategy was adopted to analyze and interpret the data. Results show that the RU has been acquiring and bundling sufficient resources and high capabilities to implement university strategies. This finding in line with the aspect of internationalization of HEIs such as managing resource, personnel and international networking, international research projects, international research outputs, student-staff mobility, and the internationality of curriculum and academic profile of institutions.Thus, this article provides a base to construct a model tailored for Malaysian Research University.